Editorial - Guenther, John (The Australian Journal of Indigenous Education, 2015)
In 2013, the Cooperative Research Centre for Remote Economic Participation's (CRC-REP) Remote Education Systems (RES) project team brought together a collection of papers built around a central theme of ‘red dirt thinking’. This theme reflected a view the authors had, that education and schooling in remote communities should be relevant to the context (that is, the ‘red dirt’) in which it is provided. We proposed this as a conceptual framework in which to challenge conventional wisdom about success, disadvantage and aspiration in remote schools.